Performance Evaluation of Rotary Dryer and Granulator in NPK Steam Granulation Plant Production Department of IIB PT Petrokimia Gresik - Kusuma, Maria Asel Pranoto; Sagala, Feni Mutiara Lasniroha; Kusworo, Tutuk Djoko; Laksono, Satrio Dwi (International Journal Labs, 2024)
PT. Petrokimia Gresik, a subsidiary of Indonesian fertilizer company PT. Indonesian Fertilizer, has three main plants: Production I, II, and III. Production IIB consists of production units Phonska IV, NPK Granulation II, III, and IV and ZK. Granulated NPK II Fertilizer is a processing unit that meets quality standards. The process involves feeding raw materials, preparing slurries, granulating, drying, screening, cooling, and screening. Supporting materials include powder coating, oil coating, and pigment. The granulation stage is crucial, where raw materials are agglomerated. The NPK Granulation Department of IIB uses various equipment, including a rotary dryer with a thermal efficiency of 79.997%. The total mass balance for the granulator, dryer, cooler, screen, and coater in NPK Granulation II for 15-15-15 fertilizer formula is 1058,096 tons/day.